2019
DOI: 10.1038/s41598-019-56887-w
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban after Thrombolysis in Acute Iliofemoral Venous Thrombosis: A Randomized, Open-labeled, Multicenter Trial

Abstract: Recently non-Vitamin K antagonist oral anticoagulants (NOAC) is replacing warfarin for the treatment of deep vein thrombosis (DVT). However, the role of NOAC after thrombolysis of acute iliofeomral DVT (IFDVT) is not yet defined. This randomized clinical trial aimed to compare the safety and efficacy of rivaroxaban versus warfarin after catheter directed thrombolysis of an IFDVT. Patients with acute DVT of both the iliac and the femoral vein (n = 72) were recruited and randomized to either standard anticoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…We hypothesized that the duration of anticoagulation with rivaroxaban in this patient might have been insufficient. In the Kang et al study, 23 the rate of thrombus recurrence was lower in the rivaroxaban group than in the warfarin group. Being the first randomized controlled study 23 on thrombolysis in acute iliofemoral venous thrombosis to compare NOAC and VKA after CDT, the results complemented previous evidence and further supported the use of rivaroxaban after CDT.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…We hypothesized that the duration of anticoagulation with rivaroxaban in this patient might have been insufficient. In the Kang et al study, 23 the rate of thrombus recurrence was lower in the rivaroxaban group than in the warfarin group. Being the first randomized controlled study 23 on thrombolysis in acute iliofemoral venous thrombosis to compare NOAC and VKA after CDT, the results complemented previous evidence and further supported the use of rivaroxaban after CDT.…”
Section: Discussionmentioning
confidence: 82%
“…In the Kang et al study, 23 the rate of thrombus recurrence was lower in the rivaroxaban group than in the warfarin group. Being the first randomized controlled study 23 on thrombolysis in acute iliofemoral venous thrombosis to compare NOAC and VKA after CDT, the results complemented previous evidence and further supported the use of rivaroxaban after CDT. One patient stopped taking the drug 4 months after discharge in this study.…”
Section: Discussionmentioning
confidence: 82%
“…In current research overall drug compliance with antithrombotic drugs was reported in 296 (77.1%) DVT patients, whereas drug compliance with rivaroxaban was present in 103 (80.5%) patients followed by heparin drug compliance in 95 (74.2%) DVT patients and warfarin drug compliance in 98 (76.6%) patients. A similar study by Kang, JM, et al, [21] reported the overall drug compliance 93.8% with antithrombotic [24] and reported the higher drug compliance with rivaroxaban followed by heparin and warfarin [25][26][27].…”
Section: Discussionmentioning
confidence: 74%
“…In current research the drug compliance with rivaroxaban was present in (54.5%) patients followed by warfarin drug compliance in (42.5%) and drug compliance with heparin was (0.0%) DVT patients and patients. A similar study by Kang, J. M., et al, reported the overall drug compliance 93.8% with antithrombotic drugs, whereas drug compliance with rivaroxaban was 100.0% and warfarin drug compliance was 93.8%[18]. Similarly, different other studies such as; Lazo-Langner, A., et al, compared the heparin and rivaroxaban, Deitelzweig, S., et al, compared the warfarin and rivaroxaban [20], Al Khateep, Y. M., et al (2019) compared the warfarin and rivaroxaban [19] and Piati, P. K., et al (2019) Comparative Analysis of Compliance between Rivaroxaban with Heparin & Warfarin in the Management of Deep Vein Thrombosis Tertiary Care Hospital Larkana compared the heparin, warfarin and rivaroxaban…”
mentioning
confidence: 64%